Perlindungan Hukum terhadap Anak Panti Asuhan yang telah Berusia Dewasa - Ida Ayu Prawita Utami Putri; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2020)
There are a lot of children who are less fortunate to be born without their parents for various reasons. An orphanage is a place where they live by self-taught in order to gain proper knowledge in order to reach maturity. With the existence of the orphanage, the government has helped facilitate all the needs of a child who is not fortunate because independently builds identity and knowledge. An orphanage is a place for children born without parents with the task of raising and providing proper education and accompanying children to adulthood and are able to sort out and choose the way forward. This research was conducted with the aim of describing the legal protection of adult orphanage children. The research method used in this research was a normative legal research method. The results of this study indicated that the orphanage guarantees child protection when the child is in the orphanage environment so that they are released from outside reach even though the child is an adult. Some orphanages make their own rules whereby a child who enters and joins as a foster child or resides in an orphanage gets a family card that is binding like a family card in general, especially if the child does not have parents, either father or mother, and a place to live.